Perfiles de Consumo de Agua Caliente Sanitaria Aplicados a un Colector Solar Tubular Plano para el Calentamiento de Agua Residencial Instalado en Bogotá - Rocha Osorio, Juan Andrés; Ávila Carranza, Carlos Mario; Solís Chaves, Juan Sebastian (TECCIENCIA, 2021)
The use of Flat Solar Collectors for the generation of Domestic Hot Water (DHW), facilitates access to this resource in an efficient, economical and sustainable way. The Sustainable Development Goals proposed by the UN, referring specifically to sustainable water management and access to renewable energy, are the main motivation for this work, since the former is an essential vital resource and its access reduces the inequality index, in developing countries such as Colombia, while the use of solar thermal energy reduces the environmental impact of the water heating process, thus reducing the consumption of electrical energy in the residential sector. Therefore, this work proposes to estimate DHW profiles through a spreadsheet that models the DHW flow thermodynamically for a whole year, making it possible to evaluate the energy performance of a Solar Collector available in the Colombian market and that is used in four types of dwellings located in the city of Bogotá. The simulation results present the DHW consumption profiles in [kg/h] per year, with DHW temperatures of up to 21 [○C], for a total transmitted irradiance of the order of 1100 [W/m2], which produces thermal energy close to 1kW. This comparative analysis allows us to review the technical and economic feasibility of solar collectors installed in single-family homes and with a DHW consumption profile close to the Colombian socio-economic reality.